Perencanaan Penghijauan dengan Menggunakan Aplikasi Sistem Informasi Geografis (SIG) (Studi kasus di Kecamatan Medan Tuntungan, Kota Medan) - Muara Tarigan; Siti Latifah; Rahmawaty Rahmawaty (Peronema Forestry Science Journal, 2016)
Urban reforestation is one of the efforts made to bring the city into an residential area that  environmentally insights with a beautiful atmosphere, harmonious and cool which can be done in many ways. Many urban lands were converted into residential functioned and shops. This research aimed to determine which area has the potential to be developed into a reforestation area. The method was divided into two phases of data collection and data processing stage. The results of this study indicated that the Medan Tuntungan district level has a greenish relatively balanced with data showing the percentage of green open space of 25.27%. Areas that could potentially be used as the location of the greening plan were Simpang Selayang Village, Tanjung Selamat Village, Lau Cih Village, Namu Gajah Village and Kemenangan Tani Village. Keywords:   Reboisation Planning, Geographic Information Systems (GIS), Medan Tuntungan District, Planning.